2012
DOI: 10.5539/jas.v4n9p57
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Potentials of Cuscuta campestris Yuncker Extracts on Germination and Growth of Radish (Raphanus sativus L.) and Lettuce (Lactuca sativa L.)

Abstract: Cuscuta campestris Yuncker, commonly known as Golden dodder is an annual problematic parasitic weed in abandoned and derelict areas in Malaysia. The weed is leafless plant, glabrous, yellow-white in colour, with haustoria, sucker-like attachments to the aerial parts of a wide range of host plants. This study was instituted to assess the allelopathic potentials of C. campestris on lettuce and radish as test plants. Three types of treatment using aqueous extract of fresh (fc), and dried s (dc) and ethanol extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
2
5
0
1
Order By: Relevance
“…Seed germination was mostly unaffected by the tested fresh weed extract of C. epithymum only in the M. sativa variety "Multifoliolate", while nonsignificant stimulating effects were only found at the highest concentrations (50 and 100 g/l -1 ). Similar results were reported by Othman et al (2012), showing that fresh plant extracts of C. campestris did not reduce seed germination of radish (R. sativus).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Seed germination was mostly unaffected by the tested fresh weed extract of C. epithymum only in the M. sativa variety "Multifoliolate", while nonsignificant stimulating effects were only found at the highest concentrations (50 and 100 g/l -1 ). Similar results were reported by Othman et al (2012), showing that fresh plant extracts of C. campestris did not reduce seed germination of radish (R. sativus).…”
Section: Resultssupporting
confidence: 88%
“…Allelopathic tolerance was detected in the varieties "Victoria", "Prista 5" and "Multifoliolate". Similar results in radish (R. sativus) and lettuce (L. sativa) were reported by Othman et al (2012). They found that the species of test plants and their varieties had different levels of susceptibility to allelopathic effects of plant extracts (from fresh or dry biomass) and that they depended on the applied concentrations.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This value was almost three times higher than that observed with extracts of A . hypogaea seeds for the same species and at the a similar concentration (less than 2.00 cm) [15]. In the evaluation of coffee fruit extracts (Coffea arabica) , the concentration required for the growth inhibition of hypocotyls and rootlets of L .…”
Section: Discussionmentioning
confidence: 99%
“…Fifty grams of fresh rhizomes, stems and leaves were cut into small pieces and oven-dried at 40 o C for 48 hours (17). The dried tissue was milled to a powder and added to 250 ml of distilled water to soak for 24 hours.…”
Section: Preparation Of Aqueous Extracts From the Dry Tissue Of A Lamentioning
confidence: 99%